SPECULOOS Northern Observatory: Searching for Red Worlds in the Northern Skies. (1st October 2022) - Burdanov, Artem Y.; Wit, Julien de; Gillon, Michaël; Rebolo, Rafael; Sebastian, Daniel; Alonso, Roi; Sohy, Sandrine; Niraula, Prajwal; Garcia, Lionel; Barkaoui, Khalid; Chinchilla, Patricia; Ducrot, Elsa; et al.
Abstract: SPECULOOS is a ground-based transit survey consisting of six identical 1 m robotic telescopes. The immediate goal of the project is to detect temperate terrestrial planets transiting nearby ultracool dwarfs (late M-dwarf stars and brown dwarfs), which could be amenable for atmospheric research with the next generation of telescopes. Here, we report the developments of the northern counterpart of the project—SPECULOOS Northern Observatory, and present its performance during the first three years of operations from mid-2019 to mid-2022. Currently, the observatory consists of one telescope, which is named Artemis. The Artemis telescope demonstrates remarkable photometric precision, allowing it to be ready to detect new transiting terrestrial exoplanets around ultracool dwarfs. Over the period of the first three years after the installation, we observed 96 objects from the SPECULOOS target list for 6000 hr with a typical photometric precision of 0.5%, and reaching a precision of 0.2% for relatively bright non-variable targets with a typical exposure time of 25 s. Our weather downtime (clouds, high wind speed, high humidity, precipitation and/or high concentration of dust particles in the air) over the period of three years was 30% of overall night time. Our actual downtime is 40% because of additional time loss associated with technical problems.